2016
DOI: 10.1038/srep38326
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Nerve Fiber Layer Thickness after Multiple Injections of Novel VEGF Decoy Receptor Conbercept for Various Retinal Diseases

Abstract: Conbercept is a recombinant fusion protein with high affinity for all vascular endothelial growth factor isoforms and placental growth factor. The repeated intravitreal injection of conbercept may cause intraocular pressure (IOP) fluctuations and long-term suppression of neurotrophic cytokines, which could lead to retinal nerve fiber layer (RNFL) damage. This retrospective fellow-eye controlled study included 98 eyes of 49 patients. The changes in IOP and RNFL thickness as well as the correlation between RNFL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…; Zhang et al. ). However, not all patients respond to anti‐VEGF intravitreal treatment equally (Lazic et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Zhang et al. ). However, not all patients respond to anti‐VEGF intravitreal treatment equally (Lazic et al.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies focused on ranibizumab, aflibercept and bevacizumab had reported similar findings ( El Chehab et al, 2016 ; Kato et al, 2019/05 ; Fuest et al, 2014 ). To the best of our knowledge, there is only one study reporting the changes of IOP after IVI of Conbercept ( Zhang et al, 2016 ). However, the main purpose of the study was to evaluate the influence of increased IOP on retinal nerve fiber thickness in a long-term basis.…”
Section: Discussionmentioning
confidence: 99%
“…Conbercept (KH902; Chengdu Kanghong Biotech Co., Ltd., Sichuan, China) is a recombinant fusion protein that was designed as a receptor decoy and has high affinity for all VEGF isoforms and placental growth factor (PlGF) [13]; it is widely used in anti-VEGF therapy in China [14, 15]. To the best of our knowledge, no study has examined the effect of conbercept on individual layer changes in DME treatment.…”
Section: Introductionmentioning
confidence: 99%